Efeito do Consumo de álcool etílico na sepse experimental - Barros, Flavia Rocha de (2011)
Alcohol is a psychoactive drug whose consumption is allowed and encouraged by society, despite the numerous health and social related. The actions of ethanol are complex and it is postulated that their heavy use alter the immune system and may increase the risk for infections such as pneumonia and complications at admission, and promoting the development of sepsis. Most septic patients exhibit at least one severe comorbidity related to its development. The comorbid alcoholism has hardly been studied. Thus, the purpose of this study was to evaluate the effect of ethanol on the development of sepsis, including its pathophysiology, through an experimental model. Three experiments were conducted. In the first experiment was analyzed mortality in a group of Wistar rats were divided into control group (n = 30) and ethanol (n = 30) receiving, respectively, water and ethanol solution (10% v / v) for four weeks . Thereafter, all animals were subjected to sepsis induced by injection technique for analysis of feces intraperitoneally survival rate. A second experiment, following the same protocol as the first, was destined for biochemical analysis, cytokine, and liver histology. We analyzed data from before and after the induction of sepsis, forming four groups each with 10 animals (C: control, E: ethanol; S: sepsis control; ES: ethanol with sepsis). To study the effects of intermittent exposure and high doses of ethanol in sepsis, a third experiment was conducted using Wistar rats were divided the same way as in Experiment 2. The results showed a significant effect of ethanol on hasten death by sepsis. This effect was dose dependent. Biochemical analysis, cytokine and liver histopathology showed important changes resulting from sepsis, validating the experimental model. The subchronic exposure to low doses of ethanol affected several parameters. Glucose and creatinine decreased and increased respectively after sepsis, but this change was more pronounced in the ethanol group (C: E: p <0.003-glucose, p <0.001-creatinine). Ethanol decreased the effect of sepsis on the production of proinflammatory cytokines (p <0.022, IL-6, p <0.003 TNF-). Liver histology showed a pattern of increased congestion and edema in the ethanol group after sepsis. The results of biochemical analysis and measurement of cytokines in the third experiment showed that alcohol interfered with important biochemical parameters such as creatinine, AST, and reduction of inflammatory cytokines (IL-6 and IL-1β). Histopathology Liver, intermittent ethanol consumption showed a greater effect on the response to sepsis that subchronic consumption, showing not only greater congestion and edema, as well as foci of cellular injury and necrosis. These differences may be involved in increasing the severity of the septic process and increased mortality among animals consuming ethanol. Given the high mortality from sepsis, and alcohol consumption encouraged by propaganda, they become more studies are needed to elucidate this interaction